2019
DOI: 10.1021/acsami.9b02136
|View full text |Cite
|
Sign up to set email alerts
|

Reliable Interlayer Based on Hybrid Nanocomposites and Carbon Nanotubes for Lithium–Sulfur Batteries

Abstract: The future energy needs have triggered research interest in finding novel energy storage systems with high energy density. Lithium–sulfur batteries are regarded as one of the most promising options for the next-generation energy storage applications because of their high theoretical energy and low cost. However, the electrochemical performances of lithium–sulfur batteries are seriously compromised by the polysulfide (LiPS) shuttling and the insulating nature of sulfur. To overcome these issues, novel CoNi1/3Fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 50 publications
0
16
0
Order By: Relevance
“…The low S content in the LFE further confirmed that it could effectively inhibit the shuttle effect and protect the Li anode during repetitive cycling. [ 28 ]…”
Section: Resultsmentioning
confidence: 99%
“…The low S content in the LFE further confirmed that it could effectively inhibit the shuttle effect and protect the Li anode during repetitive cycling. [ 28 ]…”
Section: Resultsmentioning
confidence: 99%
“…CNT-based compounds holding specific atoms that have characteristic interaction with the sulfur species via chemical bonding showed remarkable ability in preventing shuttle effect, and thus have been frequently used as an effective component in interlayers [58,59]. For example, an ultrathin and lightweight CNT/MoS 2 interlayer coated polypropylene separator was introduced to a welldesigned Li-S battery (Fig.…”
Section: Carbon Nanotubementioning
confidence: 99%
“… Physicochemical properties of the ultralight electrolyte (ULE). a) The densities of different electrolytes (Ele1: 0.1 M LiTFSI+1 wt % LiNO 3 +DME/DOL (50/50), [20] Ele2: 0.6 M LiTFSI+0.4 M LiNO 3 +DME/DOL (50/50), [5a] Ele3: 1.0 M LiTFSI+2 wt % LiNO 3 +DME/DOL (50/50), denoted as CE, [26] Ele4: 2.0 M LiTFSI+DOL, [27] Ele5: 7 m LiTFSI+DME/DOL (50/50) denoted as SIS, [28] Ele6: 1 M LiFSI+OFE/DME (95/5) [29] ). b) The electrolyte‐weight/sulfur‐weight (E g /S g ) of different electrolytes under varied E/S ratios.…”
Section: Resultsmentioning
confidence: 99%